Penggunaan Media Komik Digital Berbasis Fabel untuk Meningkatkan Keterampilan Berbicara Siswa Sekolah Dasar - Nisisari Naysa Tiffani; Anisatun Fajriah; Amalia Rachmaida Fransiska; Luthfa Nugraheni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the development of digital comic media based on fable stories as a means of improving the speaking skills of elementary school students. The background of this research is the low interest and participation of students in speaking during Indonesian language learning due to the limitations of learning media that are interesting and according to student characteristics. The research used a descriptive qualitative approach with observation, interview, and documentation techniques, conducted on third grade students in one of the elementary schools in Kudus Regency. The media was developed by inserting fable stories that are educational, fun, and contain moral values. The results showed that this media was able to increase student involvement individually and in groups. Students became more confident in expressing opinions, telling stories, and discussing. Teachers also benefited because the media was practical and relevant to the teaching materials. The media received a positive response and was considered suitable for use in learning. Fable-based digital comics are an innovative alternative in learning Indonesian, especially in improving students' speaking skills, and have the potential to be developed at other levels and subject matter.